Assessment of Aircraft Noise Emissions at International Eskisehir Hasan Polatkan Airport with Multiple Approach Model - Akdeniz,Halil Yalcin (2021)
ABSTRACT Aircraft noise emissions are a problem that negatively affects human health, directly or indirectly. For this reason, examining and managing the noise effects caused by aircrafts at the airports is important for the sustainable development of aviation. In the present study, a noise management model based on the multiapproach method, including some actions related to aircraft noise, has been created. The model was applied to the International Eskisehir Hasan Polatkan Airport (LTBY). Within the scope of the model, in the first stage, in 365 days, day, evening and night noise levels around the airport were simulated using IMMI software under the European noise directive and European Civil Aviation Conference (ECAC) doc 29-interim was also used to measure aircraft noise. In the second stage, the noise generated by the Cessna 172-S aircraft under different operating conditions experimentally measured was carried out. After the model had been applied to LTBY, improvement opportunities for aircraft noise were evaluated. It is thought that the study and its results will help other civil airports on the issue of noise problem at airports.